High-frequency properties of the electron flow slowing down in a planar diode - Pashchenko, A.V.; Melezhik, O.G.; Romanov, S.S.; Sitnikov, D.A.; Tarasov, I.K.; Tarasov, M.I.; Shapoval, I.M.; Novikov, V.E; Yatsyshin, V.A. (Вопросы атомной науки и техники, 2011)
The instability of the electron flow injected into a planar diode and slowed down in it under the action of the external electric field is investigated through the exact solution of the set of inhomogeneous hydrodynamic first-approximation equations of the stability theory. A dispersion equation has been derived, which relates the frequencies and increments (decrements) of arising electromagnetic oscillations to the parameters of the electron beam and the diode. The solution of the dispersion equation shows that in the diode, through which the slowing down electron beam is propagating, there arises the microwave oscillatory instability not described before. This instability occurs in the case when in the steady-state condition there is no potential minimum in the diode. The experiments have confirmed the occurrence of oscillatory instability with theoretically predicted frequencies and decrements in the corresponding beam and diode parameter regions.